HOMOGENIZATION OF UNREINFORCED OLD MASONRY WALL COMPARISON OF SCALAR ISOTROPIC AND ORTHOTROPIC DAMAGE MODELS - Vasco Bernardo; Tomáš Krejčí; Tomáš Koudelka; Michal Šejnoha (Acta Polytechnica CTU Proceedings)
Masonry is a heterogeneous composite material made of bricks bonded by a mortar matrix. Modeling such a material on macroscale typically calls for homogenization adopting a suitable constitutive model capable of capturing its quasi-brittle behavior. The present contribution concentrates on comparison and potential application of classical isotropic and orthotropic damage models in the framework of strain based first order numerical homogenization. As an illustrative example, a representative volume element in terms of a periodic unit cell is constructed to address the response of an unreinforced masonry (URM) structure typical of “Placa” buildings (mixed masonry-reinforced concrete buildings) built in Portugal. The performance of the two models is examined on the basis of macroscopic stress-strain curves constructed for both tensile and compressive loading. The selected geometrical constraints clearly identify the differences in the predictive capabilities of the two models.